Imagens sob Suspeita: a Censura e suas Negociações no Brasil em Tempos de Ditadura (1964-1985) - Lucas, Meize (Trabalhos de Antropologia e Etnologia, 2020)
This research proposes a reflection on the cinema censorship in Brazil during the civilian- military dictatorship (1964-1985), which is based on a range of elapsing processes in the Censorship Division of Public Amusements. Assuming that in authoritarian regimes censorship is an action aimed at interdicting discourses which point out social tensions, put into question figures of authority (such as the state, the armed forces and the church), focus political distensions or approach different forms of physical and symbolic violence, it is inquired how this interdiction (or non-interdiction) made up a negotiating field among producers, directors and distributors, on the one hand, and censors, on the other. The integrated analysis of these documents allow a comprehensive insight of the range of contests and its possible understandings.